Interfacial water intercalation-induced metal-insulator transition in NbS2/BN heterostructure. (11th March 2019) - Xu, Rui; Wang, Xinsheng; Zheng, Zhiyue; Ye, Shili; Xu, Kunqi; Lei, Le; Hussain, Sabir; Pang, Fei; Liu, Xinmeng; Li, Yan Jun; Sugawara, Yasuhiro; Ji, Wei; et al.
Abstract: Interfacial engineering, such as molecule intercalation, can modify properties and optimize performance of van der Waals heterostructures and their devices. Here, we investigated the pristine and water molecule intercalated heterointerface of niobium disulphide (NbS2 ) on hexagonal boron nitride ( h -BN) (NbS2 /BN) using advanced atomic force microscopy (AFM), and observed the metal-insulator transition (MIT) of first layer (1L-) of NbS2 induced by water molecule intercalation. In pristine sample, interfacial charge transfers were confirmed by the direct detection of trapped static charges at the post-exposed h -BN surface, produced by mechanically peeling off the 1L-NbS2 from the substrate. The interfacial charge transfers facilitate the intercalation of water molecules at the heterointerface. The intercalated water layers make a MIT of 1L-NbS2, while the pristine metallic state of the following NbS2 layers remains preserved. This work is of great significance to help understand the interfacial properties of 2D metal/insulator heterostructures and can pave the way for further preparation of an ultrathin transistor.